Dimensional Crossover Transport Induced by Substitutional Atomic Doping in SnSe2. (13th March 2018) - Lee, Suyoun; Lee, Young Tack; Park, Seong Gon; Lee, Kyu Hyoung; Kim, Sung Wng; Hwang, Do Kyung; Lee, Kimoon
Abstract: Substitutional atomic doping is one of the most convenient and precise routes to modulate semiconducting material properties. Although two‐dimensional (2D) layered transition metal dichalcogenides (TMDs) are of great interest as a prominent semiconducting material due to their unique physical/chemical properties, such a practical atomic doping is still rare, possibly due to the intrinsic localization nature of conduction paths based on d‐band states. Here, using single‐crystalline Cl‐doped SnSe2, the dimensional crossover in carrier transport accompanied by semiconductor‐to‐metal transition is reported. Nondoped SnSe2 shows semiconducting transport behavior dominated by 2D variable range hopping conduction, exhibiting relatively strong localization of carriers at low‐temperature regions. Moderately electron‐doped SnSe2 by substitution on Se with higher valent Cl exhibits superior electrical conductivity even than the heavily doped one owing to the higher electron mobility of the former (167 cm 2 V −1 s −1 at 2 K). Combined with Raman spectra, temperature dependence of mobility clearly evidences the effective screening of homopolar optical mode phonon compared to typical TMD materials. Detailed characterizations with magnetoresistance behaviors finally demonstrate that the suppression of both homopolar optical mode phonon and carrier localization as retaining low‐dimensionality is key for high mobility conduction in electron‐doped SnSe2 . Abstract : The substitutional atomic doping‐induced dimensional crossover in 2D SnSe2 is investigated in transport nature, as a prominent candidate 2D material. Through such a practical doping method, high‐electron carrier mobility is realized even under a bulky thickness without any interface fabrication, distinct from previous 2D transition‐metal dichalcogenides.